Bruceine a exerts antitumor effect against colon cancer by accumulating ROS and suppressing PI3K/Akt pathway - Zhang, Chaozheng; Cao, Yuening; Zuo, Yi; Cheng, Hongbin; Liu, Changqun; Xia, Xila; Ren, Bo; Deng, Yun; Wang, Maolin; Lu, Jun (Frontiers in Pharmacology, 2023)
Bruceine A (BA), a quassic ester from bruceine javanica, regulates diverse intracellular signal transduction pathways and manifests a variety of biological activities, however, its pharmacological mechanism in treating colon cancer (CC) is unclear. In this study we investigated the anticancer effects of BA on CC cells and the underlying mechanisms. The network pharmacology research indicated that Akt1 and Jun and PI3K/Akt pathway are the predominant targets and critical signaling pathway, respectively, for BA treatment of CC. Meanwhile, molecular docking results implied that BA could conjugate to pivotal proteins in the PI3K/Akt pathway. BA remarkably suppressed the proliferation of CC cells HCT116 and CT26 with 48-hour IC50 of 26.12 nM and 229.26 nM, respectively, and the expression of p-PI3K/p-Akt was obviously restrained by BA at the molecular level as verified by Western blot assay. Further mechanistic studies revealed BA impacted cell cycle-related proteins by regulating the expression of P27 (a protein bridging the PI3K/Akt signaling pathway with cycle-related proteins), arresting the cell cycle in the G2 phase, inhibiting the proliferation of HCT116 and CT26, and facilitated the apoptosis in CC cells by activating the mitochondria-associated apoptosis protein Bax and accumulating reactive oxygen species, in addition to BA apparently inhibited the migration of CC cells. Taken together, our results demonstrated that BA might be a promising chemotherapy drug in the treatment of CC.